Application of neurotransmitters and dental stem cells for pulp regeneration: A review - Hidayah Ramli; Norhayati Yusop; Rosmaliza Ramli; Zurairah Berahim; Roshan Peiris; Nurhafizah Ghani (Saudi Dental Journal)
Introduction: Although there have been many studies on stem cells, few have investigated how neurotransmitters and stem cell proliferation interact to regenerate dental pulp. Dental pulp regeneration is an innovative procedure for reviving dental pulp, if feasible for the entire tooth. Upon tooth injury, activated platelets release serotonin and dopamine in bulk to mobilize dental pulp stem cells to mediate natural dental repair. This has induced research on the role of neurotransmitters in increasing the proliferation rate of stem cells. This review also covers prospective future treatments for dental pulp regeneration. Methods: A literature search was performed via PubMed and ScienceDirect from 2001 to 2022, using the keywords “neurotransmitter,” “stem cell,” “tooth regeneration,” “tooth repair,” “regenerative dentistry,” and “dental pulp.” Different inclusion/exclusion criteria were used, and the search was restricted to English articles. Results: Nine publications reporting neurotransmitter interactions with stem cells for tooth and pulp regeneration were selected. Conclusion: Neurotransmitters were found to interact with dental stem cells. Evidence pointing to neurotransmitters as a factor in the increased proliferation of stem cells was found. This review thus gives hope for tooth pulp regeneration and repair.